The influence of participative budgeting on budgetary slack in composing local governments’ budget in Bali province - Widanaputra, A.A.; Mimba, N.P.S.H. (Elsevier Ltd., 2014)
This study examines the influence of participative budgeting on budgetary slack in composing nine local governments’ budget of Bali Province, using ‘career uncertainty’ as the moderating variable.The ‘career uncertainty’ has received insufficient attention in previous studies on budgetary slack.This study tries to fill this gap.Respondents of this study are 686 middle level employees.The results show that career uncertainty can moderate the relationship between participative budgeting and budgetary slack.The more certain local government employees that they will be placed at the same position in the period of budget realization, the larger the budgetary slack will be.